Filosofia da história no direito natural do Brasil império - Martins, Patrícia Carla de Melo [UNESP] (2014)
Natural Law is the area of knowledge that gave rise to the theories of Modern and Contemporary Law. This discussion has emerged in the seventeenth century by the International Maritime Law. It was later developed by the philosophers of the Enlightenment in the eighteenth century, from the perspective of Modern Absolutist State, contrary to the formation of civil society. In the nineteenth century, his approach followed the formation of constitutional governments, dialoguing with the processes of positivization of laws in each State constitutions. In the twentieth century, Natural Law fell into disuse and was replaced by the Philosophy of Law, Human Rights, International Law and the Fundamental Rights. There are several lines cooperating with Natural Law, so it did not remain restricted to a single explanatory line. Thus, the theoretical supports of Natural Law favored the construction of the conceptual categories of the State and the Nation, defining power, government, sovereignty, society, social contract, violation and penalty, family and others; the highest point of his approach was in the definition of universal human being. By the idea of the universals it was applied the axioms considered able to build social and material reality in an ethical and moral perspective superior to past and present, composing a Philosophy of History. This presentation aims to trace a brief history of Natural Law in its interface with the History of Ideas in Brazil Empire